ANALISIS KINERJA PADA POPULARITAS GIM FREE FIRE DI INDONESIA: PENDEKATAN BERBASIS KONTEN - Setianto, Diki Putra; K, Erna Ferrinadewi (Universitas Prof. Dr. Hazairin SH, 2024)
This study explores the performance and popularity of the Free Fire game in Indonesia through a content-based approach using the Technology Acceptance Model (TAM). The research aims to evaluate how TAM constructs, such as perceived usefulness and ease of use, influence user reviews and gameplay satisfaction. Secondary data from user reviews on the Google Play Store, collected between April and June 2024, were analyzed using content analysis with NVivo 12. Key findings reveal that server stability and technical performance significantly impact user satisfaction, while competitive gameplay modes enhance engagement. Frequent terms like